THERMAL-HISTORY-DEPENDENT TRANSITION IN PRESSED PELLETS OF CLO4(-)-DOPED POLY(3-METHYLTHIOPHENE) - Pereira, E. C.; Bulhoes, LOS; Pawlicka, A.; Nascimento, O. R.; Faria, R. M.; Walmsley, L. (American Physical Soc, 1994)
Electron-spin-resonance and dc conductivity data show a thermal-history-dependent transition at 240 K in pressed pellets of ClO4--doped poly(3-methylthiophene) (P3MT). We discuss the possibility of this transition to be a Peierls transition from a room-temperature-metallic to a charge-density-wave state driven by anions ordering at this temperature. Below 100 K, dc conductivity shows a change from linear to exponential decay. Nonlinear conductivity has also been observed in this system for very low electric fields.